The interplay between vector microbial community and pathogen transmission on the invasive Asian tiger mosquito, Aedes albopictus: current knowledge and future directions - Garrido, Mario; Veiga, Jesús; Garrigós, Marta; Martínez-de la Puente, Josué (Frontiers in Microbiology, 2023)
The invasive Asian tiger mosquito Aedes albopictus is nowadays broadly distributed with established populations in all continents except Antarctica. In the invaded areas, this species represents an important nuisance for humans and, more relevant, it is involved in the local transmission of pathogens relevant under a public health perspective. Aedes albopictus is a competent vector of parasites such as Dirofilaria and viruses including dengue virus, Zika virus, and chikungunya virus, among others. The mosquito microbiota has been identified as one of the major drivers of vector competence, acting upon relevant vector functions as development or immunity. Here, we review the available literature on the interaction between Ae. albopictus microbiota and pathogen transmission and identify the knowledge gaps on the topic. Most studies are strictly focused on the interplay between pathogens and Wolbachia endosymbiont while studies screening whole microbiota are still scarce but increasing in recent years, supported on Next-generation sequencing tools. Most experimental trials use lab-reared mosquitoes or cell lines, exploring the molecular mechanisms of the microbiota-pathogen interaction. Yet, correlational studies on wild populations are underrepresented. Consequently, we still lack sufficient evidence to reveal whether the microbiota of introduced populations of Ae. albopictus differ from those of native populations, or how microbiota is shaped by different environmental and anthropic factors, but especially, how these changes affect the ability of Ae. albopictus to transmit pathogens and favour the occurrence of outbreaks in the colonized areas. Finally, we propose future research directions on this research topic.